If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 = 9x + 2 + -6 Reorder the terms: 14 = 2 + -6 + 9x Combine like terms: 2 + -6 = -4 14 = -4 + 9x Solving 14 = -4 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 14 + -9x = -4 + 9x + -9x Combine like terms: 9x + -9x = 0 14 + -9x = -4 + 0 14 + -9x = -4 Add '-14' to each side of the equation. 14 + -14 + -9x = -4 + -14 Combine like terms: 14 + -14 = 0 0 + -9x = -4 + -14 -9x = -4 + -14 Combine like terms: -4 + -14 = -18 -9x = -18 Divide each side by '-9'. x = 2 Simplifying x = 2
| 1=3u-5 | | 16x^3+250=0 | | 1/2(2x-6)=4(1/4x-3/4) | | 28y+8=16 | | 6x+29=13-48 | | -7x+8+-4+-9= | | 20*log(x)=55 | | 2.00+1.50=54.5 | | -3(4v-9)+7v=4(v+6) | | 20log(x)=55 | | 2(12p+16)= | | 6=-4.1+r | | x+.06x=400 | | 268+3*g=654 | | -25.8=43v | | 268+3*g=900 | | h=15t-4.9t^2+2 | | c+4.3=-6.7 | | 5x+1=-5x-1 | | (Dy/dx)=3e^5 | | 5.6=f-64 | | 148-(56+j)=24 | | 12x-2.4.2x-1/8x.3x-4 | | 7y+-8y= | | 6.5h=39 | | 4(2x-1)=27+2(2x-5) | | 12x-2.4.2x-1/8x.3x-1 | | 73.2=6.1 | | 6x-34=100x+1 | | 6(2a-b)-15(2a-b)(2a-b)=x | | 3G+2f+9g+4g+4f= | | 4+17=10x+5 |